Ionic liquid-doped polylactic acid composite nano piezoelectric fiber membrane as well as preparation method and application thereof

By mixing doped ionic liquid with levopolylactic acid to prepare nano-piezoelectric fiber membranes, the problems of instability of electrical signal output and environmental pollution after deformation of existing piezoelectric materials are solved, and high-performance and biosafety piezoelectric materials are achieved .

CN119162730AActive Publication Date: 2024-12-20BEIJING INST OF CLOTHING TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310726758.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

The existing piezoelectric materials have unstable electrical signal output after deformation, and the non-degradable materials cause pollution to the environment, have poor biocompatibility, and are difficult to use in human-related applications.

Method used

A doped ionic liquid is mixed with levon polylactic acid to form a composite spinning liquid, and a nano-piezoelectric fiber membrane is prepared by electrospinning to improve fiber diameter uniformity and piezoelectric properties.

Benefits of technology

It significantly improves the piezoelectric properties of L-polylactic acid, realizes the stability and biosafety of the material, reduces environmental pollution, and promotes its application in the piezoelectric field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004293141250000011
    Figure HDA0004293141250000011
  • Figure HDA0004293141250000012
    Figure HDA0004293141250000012
  • Figure HDA0004293141250000021
    Figure HDA0004293141250000021
Patent Text Reader

Abstract

The invention discloses an ionic liquid-doped polylactic acid composite nano piezoelectric fiber membrane which is obtained by adding an ionic liquid into a poly-L-lactic acid solution to obtain a composite spinning solution and carrying out electrostatic spinning. The preparation process of the polylactic acid composite nano piezoelectric fiber membrane doped with the ionic liquid is simple and easy to implement, and the piezoelectric property of polylactic acid is effectively improved so as to meet the use requirements of people.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of piezoelectric materials, and in particular relates to a polylactic acid composite nanometer piezoelectric fiber film doped with an ionic liquid used as a piezoelectric material and a preparation method thereof. Background Art

[0002] With the development of society and people's emphasis on health, it is of great significance to develop self-powered flexible products suitable for smart wearable electronic devices to monitor the human body's movement status in real time. Piezoelectric materials are self-powered materials that can convert mechanical energy into electrical energy. They can still maintain electrical signal output under large deformation and can be used in sensors, actuators, energy collection, etc.

[0003] Common piezoelectric materials include piezoelectric ceramics such as lead zirconate titanate and barium titanate (BaTiO3) and piezoelectric polymers such as polyvinyl chloride (PVC), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), and left-handed polylactic acid (PLLA). Piezoelectric materials can be divided into two categories according to their piezoelectric principles: one is to achieve their piezoelectricity through high electric field polarization. Taking PVDF as an example, it is usually necessary to apply voltage to polarize it in its high-temperature molten state, and remove the electric field after it is completely cooled and fixed to freeze the polarized state. However, due to the relaxation characteristics of the polymer, this semi-permanent electret cannot maintain its piezoelectric properties for a long time; another type of piezoelectric polymer is composed of chiral molecular chains, which do not require polarization treatment with an external electric field. Polarization can be achieved by rotating the chiral center through mechanical action. For example, polylactic acid with chiral repeating units can exhibit certain shear piezoelectricity. Although the first type of piezoelectric ceramics and piezoelectric polymers (PVDF, etc.) have better piezoelectric properties, they need to be polarized by an external electric field to obtain excellent piezoelectric properties; secondly, non-degradable or difficult-to-degrade piezoelectric polymers will become microplastics after entering the natural cycle, causing secondary pollution to the ecological environment. This will not only be difficult to maintain for a long time as fossil resources are increasingly depleted, but also cause environmental problems such as carbon emissions and white pollution. In addition, common piezoelectric materials have poor biocompatibility and usually have high biological toxicity, making them difficult to use in applications related to the human body, such as bone tissue repair and piezoelectric teeth whitening.

[0004] Among them, L-polylactic acid (PLLA) is an important biodegradable piezoelectric polymer, and its piezoelectricity comes from the rotation of the polar group ester group in the molecule. However, the piezoelectric performance of polylactic acid materials is currently poor, so in order to improve its piezoelectric performance, it is necessary to develop and prepare PLLA piezoelectric materials with excellent performance. Summary of the invention

[0005] To solve the above problems, the present invention provides a polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquids, wherein ionic liquids (ILs) are added to a L-polylactic acid solution to form a composite spinning solution, and the polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquids is obtained by electrospinning. The fiber diameter in the fiber membrane is smaller than that of a single L-polylactic acid, the diameter is more uniform, and the piezoelectric performance is significantly improved, thereby completing the present invention.

[0006] The object of the present invention is to provide a polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquid.

[0007] The polylactic acid is preferably L-polylactic acid.

[0008] The ionic liquid is selected from one or more of imidazole ionic liquids and organic phosphate ionic liquids.

[0009] The present invention also aims to provide a method for preparing the polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquids. The method comprises adding ionic liquids (ILs) to a left-handed polylactic acid solution to obtain a composite spinning solution, and electrospinning to obtain the polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquids.

[0010] The present invention has the following beneficial effects:

[0011] (1) In the present invention, L-polylactic acid is mixed with an ionic liquid to form a composite spinning solution. The piezoelectric properties of the piezoelectric fiber membrane obtained by spinning are significantly improved and the piezoelectric properties are stable, which can realize the promotion and application of L-polylactic acid in the piezoelectric field and reduce the pollution of traditional piezoelectric polymer materials.

[0012] (2) The preparation process of the present invention is simple, easy to implement and control, and the performance of the obtained polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquid is easy to be homogenized, which is conducive to practical application.

[0013] (3) The present invention uses polylactic acid as the base material, which can achieve degradation, reduce environmental pollution, and enhance the biosafety of the material compared to polymer materials such as polyvinyl chloride (PVC), polyacrylonitrile (PAN), and polyvinylidene fluoride (PVDF). BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The XRD spectra of the PLLA piezoelectric fiber film prepared in the comparative example and the PLLA-5% [EMIm] [PF6] prepared in Example 1 are shown;

[0015] Figure 2The infrared spectra of the PLLA piezoelectric fiber film prepared in the comparative example and PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6] prepared in Example 1 are shown;

[0016] Figure 3 The conductivity change curves of the composite spinning solutions in the process of preparing the PLLA piezoelectric fiber membrane in the comparative example and preparing PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6] in Example 1 are shown;

[0017] Figure 4 The conductivity change curves of the composite spinning solutions in the process of preparing PLLA piezoelectric fiber membranes in the comparative example and preparing PLLA / [EMIm][Cl], PLLA / [EMIm][BF4], PLLA / [EMIm][PF6], PLLA / [EMIm][HSO4], PLLA / [EMIm][OAc], and PLLA / [EMIm][NTf2] in the examples are shown;

[0018] Figure 5 The PLLA piezoelectric fiber film prepared in the comparative example and the PLLA / [N 2222 Conductivity change curves of the composite spinning solutions during the processes of ][PF6], PLLA / [EPy][PF6], PLLA / [BPy][PF6], PLLA / [MMIm][PF6], PLLA / [EMIm][PF6], PLLA / [BMIm][PF6], and PLLA / [OMIm][PF6];

[0019] Figure 6 Piezoelectric test curves of PLLA piezoelectric fiber film, PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6] are shown;

[0020] Figure 7Piezoelectric test curves of PLLA piezoelectric fiber film, PLLA / [EMIm][Cl], PLLA / [EMIm][BF4], PLLA / [EMIm][PF6], PLLA / [EMIm][HSO4], PLLA / [EMIm][OAc], and PLLA / [EMIm][NTf2] are shown;

[0021] Figure 8 The PLLA piezoelectric fiber film, PLLA / [N 2222 [PF6], PLLA / [EPy][PF6], PLLA / [BPy][PF6], PLLA / [MMIm][PF6], PLLA / [EMIm][PF6], PLLA / [BMIm][PF6], PLLA / [OMIm][PF6] piezoelectric test curves;

[0022] Figure 9-1 a to Figure 9-2 g shows the SEM images and fiber diameter distribution diagram of PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6], wherein Figure 9-1 a is PLLA piezoelectric fiber film, Figure 9-1 b is PLLA-0.5%[EMIm][PF6], Figure 9-1 c is PLLA-1%[EMIm][PF6], Figure 9-1 d is PLLA-1.5%[EMIm][PF6], Figure 9-2 e is PLLA-2%[EMIm][PF6], Figure 9-2 f is PLLA-5%[EMIm][PF6], Figure 9-2 g is PLLA-8%[EMIm][PF6];

[0023] Figure 10-1 a to Figure 10-2 g shows the SEM images and fiber diameter distribution diagram of PLLA / [EMIm][Cl], PLLA / [EMIm][BF4], PLLA-5%[EMIm][PF6], PLLA / [EMIm][HSO4], PLLA / [EMIm][OAc], and PLLA / [EMIm][NTf2], wherein Figure 10-1 a is PLLA piezoelectric fiber film, Figure 10-1 b is PLLA / [EMIm][Cl], Figure 10-1 c is PLLA / [EMIm][BF4], Figure 10-1 d is PLLA-5%[EMIm][PF6], Figure 10-2 e is PLLA / [EMIm][HSO4], Figure 10-2 f is PLLA / [EMIm][OAc], Figure 10-2 g is PLLA / [EMIm][NTf2];

[0024] Figure 11-1 a to Figure 11-2 g shows PLLA / [N 2222 SEM images and fiber diameter distribution diagrams of ][PF6], PLLA / [EPy][PF6], PLLA / [BPy][PF6], PLLA / [MMIm][PF6], PLLA-5%[EMIm][PF6], PLLA / [BMIm][PF6], and PLLA / [OMIm][PF6], among which Figure 11-1 a is PLLA piezoelectric fiber film, Figure 11-1 b is PLLA / [N 2222 ][PF6], Figure 11-1 c is PLLA / [EPy][PF6], Figure 11-1 d is PLLA / [BPy][PF6], Figure 11-2 e is PLLA / [MMIm][PF6], Figure 11-2 f is PLLA-5%[EMIm][PF6], Figure 11-2 g is PLLA / [BMIm][PF6], Figure 11-2 h is PLLA / [OMIm][PF6];

[0025] Fig.12 A piezoelectric stability test graph of a piezoelectric sensor prepared from PLLA / [EMIm][PF6] (PLLA-2%[EMIm][PF6]) is shown. DETAILED DESCRIPTION

[0026] The present invention will be further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present invention will become more clear and distinct.

[0027] The invention provides a polylactic acid composite nanometer piezoelectric fiber membrane doped with an ionic liquid.

[0028] The polylactic acid is preferably L-polylactic acid.

[0029] The ionic liquid is selected from one or more of imidazole ionic liquids and organic phosphate ionic liquids, preferably one or more of 1-ethyl-3-methylimidazolium ionic liquids and hexafluorophosphate ionic liquids, more preferably 1-ethyl-3-methylimidazolium hexafluorophosphate ([EMIm][PF6]), 1-ethyl-3-methylimidazolium chloride ([EMIm][Cl]), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIm][BF4]), 1-ethyl-3-methylimidazolium hydrogen sulfate ([EMIm][HSO4]), 1-ethyl-3-methylimidazolium acetate ([EMIm][OAc]), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIm][NTf2]), tetraethylammonium hexafluorophosphate ([N 2222 [PF6]), N-ethylpyridinium hexafluorophosphate ([EPy][PF6]), N-butylpyridinium hexafluorophosphate ([BPy][PF6]), 1,3-dimethylimidazolium hexafluorophosphate ([MMIm][PF6]), 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF6]) and 1-octyl-3-methylimidazolium hexafluorophosphate ([OMIm][PF6]), such as 1-ethyl-3-methylimidazolium hexafluorophosphate ([EMIm][PF6]).

[0030] The present invention also provides a method for preparing the polylactic acid composite nanometer piezoelectric fiber membrane doped with ionic liquids. The method comprises adding ionic liquids (ILs) into a left-handed polylactic acid solution to obtain a composite spinning solution, and electrospinning to obtain the polylactic acid composite nanometer piezoelectric fiber membrane doped with ionic liquids.

[0031] The viscosity average molecular weight of the L-polylactic acid is 1.3×10 5 ~2.0×10 5 g / mol, preferably 1.5×10 5 ~2.4×10 5 g / mol, more preferably 1.7×10 5 ~2.0×10 5 g / mol.

[0032] In the L-polylactic acid solution, the solvent is selected from one or more of halogenated alkane solvents, alcohol solvents and amide solvents, preferably selected from one or more of dichloromethane, chloroform, dichloroethane, dichloropropane, hexafluoroisopropanol and N,N-dimethylformamide, more preferably a mixed solvent of dichloromethane and hexafluoroisopropanol.

[0033] Preferably, in the mixed solvent of dichloromethane (DCM) and hexafluoroisopropanol (HFIP), the volume ratio of the two is (4-11):3, preferably (5-9):3, and more preferably (6-7):3.

[0034] The concentration of the polylactic acid solution is 0.04-0.6 g / mL, preferably 0.07-0.4 g / mL, and more preferably 0.1-0.2 g / mL.

[0035] In the composite spinning solution, the concentration of the ionic liquid is 0.3-11wt%, preferably 0.4-8wt%, and more preferably 0.5-5wt%. The conductivity of the spinning solution increases with the increase of the ionic liquid concentration. Only when the ionic liquid concentration is within a certain range and the conductivity of the spinning solution is maintained within a suitable range, a nanofiber membrane with good fiber morphology can be successfully prepared.

[0036] During the electrospinning process, the spinning voltage is 10-28 kV, preferably 13-24 kV, and more preferably 16-20 kV; the spinning speed is 0.04-0.18 mL / h, preferably 0.06-0.15 mL / h, and more preferably 0.08-0.12 mL / h; the spinning time is 6-16 h, preferably 7-14 h, and more preferably 8-12 h; the receiving roller speed is 60-160 r / min, preferably 70-140 r / min, and more preferably 80-120 r / min.

[0037] In the polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquid, the fiber diameter is 60 to 500 nm, preferably 80 to 400 nm, and more preferably 100 to 300 nm.

[0038] Example

[0039] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.

[0040] In the following examples, polylactic acid (PLLA) was purchased from Zhejiang Hisun Biomaterials Co., Ltd., model number REVODE190 (viscosity average molecular weight 1.85×10 5 g / mol).

[0041] Hexafluoroisopropanol (HFIP, 99%) was purchased from Beijing Inokai Technology Co., Ltd. Dichloromethane (DCM, analytical grade) was purchased from Beijing Chemical Reagent Co., Ltd.

[0042] 1-Ethyl-3-methylimidazolium hexafluorophosphate ([EMIm][PF6], 99%), 1-Ethyl-3-methylimidazolium chloride ([EMIm][Cl], 99%), 1-Ethyl-3-methylimidazolium tetrafluoroborate ([EMIm][BF4], 99%), 1-Ethyl-3-methylimidazolium hydrogen sulfate ([EMIm][HSO4], 99%), 1-Ethyl-3-methylimidazolium acetate ([EMIm][OAc], 99%), 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIm][NTf2], 99%), tetraethylammonium hexafluorophosphate ([N 2222 ][PF6], 99%), N-ethylpyridinium hexafluorophosphate ([EPy][PF6], 99%), N-butylpyridinium hexafluorophosphate ([BPy][PF6], 99%), 1,3-dimethylimidazole hexafluorophosphate ([MMIm][PF6], 99%), 1-butyl-3-methylimidazole hexafluorophosphate ([BMIm][PF6], 99%), and 1-octyl-3-methylimidazole hexafluorophosphate ([OMIm][PF6], 99%) were purchased from Qingdao Olike New Material Technology Co., Ltd.

[0043] Example 1

[0044] 1.6 g PLLA and [EMIm][PF6] were added to 10 mL of a mixed solvent of DCM and HFIP (volume ratio V DCM :V HFIP =7:3), stirred and dissolved at 30°C to obtain a PLLA / [EMIm][PF6] composite spinning solution. The concentration of [EMIm][PF6] in the PLLA / [EMIm][PF6] composite spinning solution was adjusted to 0.5wt%, 1wt%, 1.5wt%, 2wt%, 5wt%, and 8wt%.

[0045] A high-voltage electrospinning machine was used with aluminum foil as the substrate. The above-mentioned composite spinning solution was spun under the same spinning conditions (receiving roller speed 100 r / min, spinning voltage 18 kV, spinning speed 0.1 mL / h, spinning distance 15 cm, spinning time 10 h) to prepare composite nano piezoelectric fiber membranes PLLA / [EMIm][PF6]: PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6].

[0046] Example 2

[0047] A composite nano-piezoelectric fiber membrane PLLA / [EMIm][Cl] was prepared according to the method in Example 1, with the only difference being that [EMIm][Cl] was added instead of [EMIm][PF6] so that the concentration of [EMIm][Cl] in the composite spinning solution was 5 wt%.

[0048] Example 3

[0049] The composite nano-piezoelectric fiber membrane PLLA / [EMIm][BF4] was prepared according to the method in Example 2, with the only difference being that [EMIm][BF4] was added instead of [EMIm][Cl].

[0050] Example 4

[0051] The composite nano-piezoelectric fiber membrane PLLA / [EMIm][HSO4] was prepared according to the method in Example 2, except that [EMIm][HSO4] was added instead of [EMIm][Cl].

[0052] Example 5

[0053] The composite nano-piezoelectric fiber membrane PLLA / [EMIm][OAc] was prepared according to the method in Example 2, except that [EMIm][OAc] was added instead of [EMIm][Cl].

[0054] Example 6

[0055] The composite nano-piezoelectric fiber membrane PLLA / [EMIm][NTf2] was prepared according to the method in Example 2, with the only difference being that [EMIm][NTf2] was added instead of [EMIm][Cl].

[0056] Example 7

[0057] The composite nano-piezoelectric fiber membrane PLLA / [N 2222 ][PF6], the only difference is: add [N 2222 ][PF6] replaces [EMIm][Cl].

[0058] Example 8

[0059] The composite nano-piezoelectric fiber membrane PLLA / [EPy][PF6] was prepared according to the method in Example 2, except that [EPy][PF6] was added instead of [EMIm][Cl].

[0060] Example 9

[0061] The composite nano-piezoelectric fiber membrane PLLA / [BPy][PF6] was prepared according to the method in Example 2, except that [BPy][PF6] was added instead of [EMIm][Cl].

[0062] Example 10

[0063] The composite nano-piezoelectric fiber membrane PLLA / [MMIm][PF6] was prepared according to the method in Example 2, with the only difference being that [MMIm][PF6] was added instead of [EMIm][Cl].

[0064] Embodiment 11

[0065] The composite nano-piezoelectric fiber membrane PLLA / [BMIm][PF6] was prepared according to the method in Example 2, except that [BMIm][PF6] was added instead of [EMIm][Cl].

[0066] Example 12

[0067] The composite nano-piezoelectric fiber membrane PLLA / [OMIm][PF6] was prepared according to the method in Example 2, except that [OMIm][PF6] was added instead of [EMIm][Cl].

[0068] Comparative Example

[0069] A PLLA piezoelectric fiber membrane was prepared according to the method in Example 1, except that the ionic liquid [EMIm][PF6] was not added.

[0070] Experimental example

[0071] Experimental Example 1

[0072] The PLLA piezoelectric fiber membrane prepared in the comparative example and the PLLA-5% [EMIm] [PF6] prepared in Example 1 were subjected to X-ray diffraction (XRD) analysis (X-ray diffractometer was D8 DISCOVER from Bruker, Germany). The test spectra were as follows: Figure 1 shown.

[0073] from Figure 1 It can be seen that there is no obvious characteristic peak in the spectrum of PLLA-5%[EMIm][PF6], indicating that the prepared PLLA-5%[EMIm][PF6] is not crystallized.

[0074] Experimental Example 2

[0075] The PLLA piezoelectric fiber membranes prepared in the comparative example and the PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6] prepared in Example 1 were tested by Fourier infrared spectroscopy. The test results are as follows: Figure 2 shown.

[0076] from Figure 2 It can be seen that the characteristic peak of carbonyl group belonging to PLLA has shifted from 1754.1cm -1 Offset to 1756.9cm -1 , indicating that there is a synergistic effect between PLLA and ionic liquid [EMIm][PF6].

[0077] Experimental Example 3

[0078] The conductivity of the composite spinning solution during the preparation of the PLLA piezoelectric fiber membrane in the comparative example and the preparation of PLLA-0.5% [EMIm] [PF6], PLLA-1% [EMIm] [PF6], PLLA-1.5% [EMIm] [PF6], PLLA-2% [EMIm] [PF6], PLLA-5% [EMIm] [PF6], and PLLA-8% [EMIm] [PF6] in Example 1 was measured using a conductivity meter (DDS-11A, Shanghai Yidian Scientific Instrument Co., Ltd.). The test results are as follows: Figure 3 shown.

[0079] from Figure 3 It can be seen that the conductivity of the composite spinning solution increases with the increase of the amount of ionic liquid added.

[0080] Experimental Example 4

[0081] The PLLA piezoelectric fiber membranes were prepared in the comparative examples, and the PLLA / [EMIm][Cl], PLLA / [EMIm][BF4], PLLA / [EMIm][PF6] (PLLA-5%[EMIm][PF6]), PLLA / [EMIm][HSO4], PLLA / [EMIm][OAc], PLLA / [EMIm][NTf2], PLLA / [N 2222The conductivity of the composite spinning solution in the processes of ][PF6], PLLA / [EPy][PF6], PLLA / [BPy][PF6], PLLA / [MMIm][PF6], PLLA / [BMIm][PF6], and PLLA / [OMIm][PF6] was tested using a conductivity meter (DDS-11A, Shanghai Yidian Scientific Instrument Co., Ltd.). The test results are shown in Figure 4 and Figure 5 shown.

[0082] from Figure 4 and Figure 5 It can be seen that the conductivity of the PLLA spinning solution is significantly improved after adding ionic liquid.

[0083] Experimental Example 5

[0084] Piezoelectric tests were performed on the PLLA piezoelectric fiber film prepared in the comparative example and PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6] prepared in Example 1.

[0085] Two pieces of aluminum foil were placed on both sides of the PLLA piezoelectric fiber film or the composite nano-piezoelectric fiber film, pressed tightly, as electrodes, and then two copper strips were drawn out from the electrodes and connected to the wires. The device was packaged with tape to make a piezoelectric sensor. A linear motor (Gaochuang Transmission Technology Development Co., Ltd.) was used as a force-applying device to continuously strike the piezoelectric sensor at a rate of 2s / time with a pressure of 5N. An electrometer (6514, Keithley Instruments, USA) was used to collect the electrical signal output by the sensor. The test results are shown in the figure. Figure 6 shown.

[0086] from Figure 6 It can be seen that with the gradual increase of the addition amount of [EMIm][PF6], the piezoelectric properties of the composite nano piezoelectric fiber membrane first increase and then decrease. When the addition amount of [EMIm][PF6] is 2wt%, the piezoelectric properties of the composite nano piezoelectric fiber membrane are optimal, and the output voltage is 4 times that of the PLLA piezoelectric fiber membrane.

[0087] Experimental Example 6

[0088] The PLLA piezoelectric fiber films prepared in the comparative examples, PLLA / [EMIm][Cl], PLLA / [EMIm][BF4], PLLA / [EMIm][PF6] (PLLA-5%[EMIm][PF6]), PLLA / [EMIm][HSO4], PLLA / [EMIm][OAc], PLLA / [EMIm][NTf2], PLLA / [N 2222 ][PF6], PLLA / [EPy][PF6], PLLA / [BPy][PF6], PLLA / [MMIm][PF6], PLLA / [BMIm][PF6], and PLLA / [OMIm][PF6] were subjected to piezoelectric testing.

[0089] Two pieces of aluminum foil were placed on both sides of the PLLA piezoelectric fiber film or the composite nano-piezoelectric fiber film, pressed tightly, as electrodes, and then two copper strips were drawn out from the electrodes and connected to the wires. The device was packaged with tape to make a piezoelectric sensor. A linear motor (Gaochuang Transmission Technology Development Co., Ltd.) was used as a force-applying device to continuously tap the sensor at a rate of 2s / time. An electrometer (6514, Keithley Instruments, USA) was used to collect the electrical signal output by the sensor. The test results are shown in the figure. Figure 7 and Figure 8 shown.

[0090] Figure 7 and Figure 8 It can be seen that the piezoelectric properties of the composite nanopiezoelectric fiber membrane doped with ionic liquid are significantly better than those of the PLLA piezoelectric fiber membrane. At the same time, it can be seen that changing the anion and cation structure of the ionic liquid will affect the piezoelectric properties of the composite nanopiezoelectric fiber membrane, and the piezoelectric properties of the composite nanopiezoelectric fiber membrane doped with [EMIm][PF6] are the best.

[0091] The piezoelectric sensor made of PLLA / [EMIm][PF6] (PLLA-2%[EMIm][PF6]) was repeatedly tested for piezoelectricity. The test results are as follows: Fig.12 As shown in the figure, it can be seen that the piezoelectric stability of the piezoelectric sensor is good.

[0092] Experimental Example 7

[0093] Scanning electron microscopy (SEM) analysis was performed on the PLLA piezoelectric fiber membrane prepared in the comparative example and the PLLA-0.5% [EMIm] [PF6], PLLA-1% [EMIm] [PF6], PLLA-1.5% [EMIm] [PF6], PLLA-2% [EMIm] [PF6], PLLA-5% [EMIm] [PF6], and PLLA-8% [EMIm] [PF6] prepared in Example 1, and the fiber diameters in the fiber membrane were statistically analyzed. The specific SEM images and fiber diameter distribution diagrams are shown in FIG. Figure 9-1 a to Figure 9-2 g shown Figure 9-1 a is PLLA piezoelectric fiber film, Figure 9-1 b is PLLA-0.5%[EMIm][PF6], Figure 9-1 c is PLLA-1%[EMIm][PF6], Figure 9-1 d is PLLA-1.5%[EMIm][PF6], Figure 9-2 e is PLLA-2%[EMIm][PF6], Figure 9-2 f is PLLA-5%[EMIm][PF6], Figure 9-2 g is PLLA-8%[EMIm][PF6]).

[0094] The average fiber diameters of PLLA piezoelectric fiber film, PLLA-0.5%[EMIm][PF6], PLLA-1%[EMIm][PF6], PLLA-1.5%[EMIm][PF6], PLLA-2%[EMIm][PF6], PLLA-5%[EMIm][PF6], and PLLA-8%[EMIm][PF6] are 1157nm, 205nm, 167nm, 142nm, 174nm, 162nm, and 172nm, respectively.

[0095] As can be seen from Figure 9, the doping of [EMIm][PF6] is beneficial to the reduction of PLLA fiber diameter, and as the amount of ionic liquid added increases, adhesion occurs between the fibers.

[0096] The PLLA / [EMIm][Cl], PLLA / [EMIm][BF4], PLLA-5%[EMIm][PF6], PLLA / [EMIm][HSO4], PLLA / [EMIm][OAc], PLLA / [EMIm][NTf2] and PLLA / [N 2222[PF6], PLLA / [EPy][PF6], PLLA / [BPy][PF6], PLLA / [MMIm][PF6], PLLA / [BMIm][PF6], and PLLA / [OMIm][PF6] were subjected to SEM analysis, and the fiber diameters in the fiber membranes were statistically analyzed. The specific SEM images and fiber diameter distribution diagrams are shown in Figures 10 and 11 ( Figure 10-1 a is PLLA piezoelectric fiber film, Figure 10-1 b is PLLA / [EMIm][Cl], Figure 10-1 c is PLLA / [EMIm][BF4], Figure 10-1 d is PLLA-5%[EMIm][PF6], Figure 10-2 e is PLLA / [EMIm][HSO4], Figure 10-2 f is PLLA / [EMIm][OAc], Figure 10-2 g is PLLA / [EMIm][NTf2];

[0097] Figure 11-1 a is PLLA piezoelectric fiber film, Figure 11-1 b is PLLA / [N 2222 ][PF6], Figure 11-1 c is PLLA / [EPy][PF6], Figure 11-1 d is PLLA / [BPy][PF6], Figure 11-2 e is PLLA / [MMIm][PF6], Figure 11-2 f is PLLA-5%[EMIm][PF6], Figure 11-2 g is PLLA / [BMIm][PF6], Figure 11-2 h is PLLA / [OMIm][PF6]).

[0098] As can be seen from FIG. 10 and FIG. 11 , the diameter of the composite nanofibers doped with ionic liquid is smaller than that of the PLLA fibers, and the diameter is usually 100 to 300 nm, and the diameter distribution is uniform.

[0099] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A polylactic acid composite nano-piezoelectric fiber membrane doped with an ionic liquid, wherein the polylactic acid is L-polylactic acid, and the ionic liquid is selected from one or more of imidazole ionic liquids and organic phosphate ionic liquids.

2. The piezoelectric fiber membrane according to claim 1, characterized in that: The ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium ionic liquids and hexafluorophosphate ionic liquids, preferably 1-ethyl-3-methylimidazolium hexafluorophosphate ([EMIm][PF6]), 1-ethyl-3-methylimidazolium chloride ([EMIm][Cl]), 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIm][BF4]), 1-ethyl-3-methylimidazolium hydrogen sulfate ([EMIm][HSO4]), 1-ethyl-3-methylimidazolium acetate ([EMIm][OAc]), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIm][NTf2]), tetraethylammonium hexafluorophosphate ([N 2222 [PF6]), N-ethylpyridinium hexafluorophosphate ([EPy][PF6]), N-butylpyridinium hexafluorophosphate ([BPy][PF6]), 1,3-dimethylimidazolium hexafluorophosphate ([MMIm][PF6]), 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF6]) and 1-octyl-3-methylimidazolium hexafluorophosphate ([OMIm][PF6]).

3. The piezoelectric fiber membrane according to claim 1, characterized in that: In the polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquid, the fiber diameter is 60 to 500 nm, preferably 80 to 400 nm, and more preferably 100 to 300 nm.

4. A method for preparing the polylactic acid composite nano-piezoelectric fiber membrane doped with ionic liquid according to claim 1, characterized in that: The method adds ionic liquid into a left-handed polylactic acid solution to obtain a composite spinning solution, and electrospinning is performed to obtain a polylactic acid composite nanometer piezoelectric fiber membrane doped with the ionic liquid.

5. The method according to claim 4, characterized in that In the L-polylactic acid solution, the solvent is selected from one or more of halogenated alkane solvents, alcohol solvents and amide solvents, preferably selected from one or more of dichloromethane, chloroform, dichloroethane, dichloropropane, hexafluoroisopropanol and N,N-dimethylformamide, more preferably a mixed solvent of dichloromethane and hexafluoroisopropanol.

6. The method according to claim 4, characterized in that The concentration of the polylactic acid solution is 0.04-0.6 g / mL, preferably 0.07-0.4 g / mL, and more preferably 0.1-0.2 g / mL.

7. The method according to claim 4, characterized in that In the composite spinning solution, the concentration of the ionic liquid is 0.3-11 wt %, preferably 0.4-8 wt %, and more preferably 0.5-5 wt %.

8. The method according to claim 4, characterized in that During the electrospinning process, the spinning voltage is 10-28 kV, preferably 13-24 kV, and more preferably 16-20 kV.

9. The method according to claim 4, characterized in that During the electrospinning process, the spinning speed is 0.04-0.18 mL / h, preferably 0.06-0.15 mL / h, more preferably 0.08-0.12 mL / h; the spinning time is 6-16 h, preferably 7-14 h, more preferably 8-12 h.

10. The method according to claim 4, characterized in that During the electrospinning process, the receiving roller rotates at a speed of 60-160 r / min, preferably 70-140 r / min, and more preferably 80-120 r / min.

Citation Information

Patent Citations

  • Anti-static high-beta-crystal-content polyvinylidene fluoride nanometer composite fiber film and preparation method thereof

    CN103556234A

  • Application of poly-L-lactic acid fiber material in piezoelectric devices

    CN107293639A

  • Ion dipoles containing polymer compositions

    CN108352441A

  • PVDF / ionic liquid / PSU high-efficiency low-resistance filtering membrane and preparation method thereof

    CN110433674A

  • Polyacrylonitrile composite nanofiber membrane and preparation method and application thereof

    CN113802266A